2020
DOI: 10.2147/cmar.s263383
|View full text |Cite
|
Sign up to set email alerts
|

<p>LncRNA PVT1 Regulates TRPS1 Expression in Breast Cancer by Sponging miR-543</p>

Abstract: Background Breast cancer is the most common female malignancy with high invasion and metastasis abilities. Studies have shown that long non-coding RNA (lncRNA) plasmacytoma variant translocation 1 gene (PVT1) is an oncogene and is positively correlated with progression and metastasis of breast tumors. However, the detailed mechanism of PVT1 in breast cancer tumorigenesis is not fully understood. Methods Real-time polymerase quantitative chain reaction (RT-qPCR) was perf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 24 publications
1
15
0
Order By: Relevance
“…Multiple mechanisms have been described in order to understand PVT1 ’s role in breast tumorigenesis. PVT1 suppression enhanced TRPS1 levels by negatively targeting miR-543 in BC [ 238 ]. PVT1 binds KLF5, an interaction that is enhanced by BAP1 (BRCA1-associated protein), to upregulate beta-catenin signaling and promote TNBC tumorigenesis [ 237 ].…”
Section: Resultsmentioning
confidence: 99%
“…Multiple mechanisms have been described in order to understand PVT1 ’s role in breast tumorigenesis. PVT1 suppression enhanced TRPS1 levels by negatively targeting miR-543 in BC [ 238 ]. PVT1 binds KLF5, an interaction that is enhanced by BAP1 (BRCA1-associated protein), to upregulate beta-catenin signaling and promote TNBC tumorigenesis [ 237 ].…”
Section: Resultsmentioning
confidence: 99%
“…By intersecting the miRNA list of GSE113740 (selection criteria: adjusted P < 0.05, |logFC|≥1) and that of GSE146477 (selection criteria: adjusted P < 0.05, |log 2 FC|≥1), miR-543 was identified as the candidate miRNA that may participate in breast cancer pathogenesis ( Figure 1a ). miR-543 was a significant suppressor of breast cancer [ 6 , 24 , 25 ]. Nonetheless, the study of miR-543 in breast cancer is still limited.…”
Section: Resultsmentioning
confidence: 99%
“…Several studies have shown the connection between PVT1 and different miRNAs in breast cancer. PVT1 functions as a sponge to regulate miR-543 ( 111 ), which is a known tumor suppressor miRNA in breast cancer ( 112 ). The tumorigenic potency of PVT1 could be abrogated by miR-543 overexpression, and loss of PVT1 is associated with inhibition of growth, increased apoptosis, and decreased tumor size ( 111 ).…”
Section: Oncogenic Lncrnasmentioning
confidence: 99%
“…PVT1 functions as a sponge to regulate miR-543 ( 111 ), which is a known tumor suppressor miRNA in breast cancer ( 112 ). The tumorigenic potency of PVT1 could be abrogated by miR-543 overexpression, and loss of PVT1 is associated with inhibition of growth, increased apoptosis, and decreased tumor size ( 111 ). A cluster of oncogenes (miR-1204, 1205, 1206, 1207-3p, 1207-5p, 1208) at the 8q24.21 locus is regulated by PVT1 ( 193 ).…”
Section: Oncogenic Lncrnasmentioning
confidence: 99%